Simulation and Visualization of TSP Using Ant Colony Optimization - Tri Basuki, Kurniawan; Misinem, .; Astried, .; Joan Angelina, Widians (INTI International University, 2023)
The Travelling Salesman Problem (TSP) is a well-known algorithmic problem its main objective is optimization. While naturally, it will require a significant amount of time and effort to finish a lot of complex work by hand such as TSP, one of the most exciting advances in software development is the discovery of optimization algorithms. When we are presented with a difficult assignment, optimization techniques can be used to ensure that the complex work is completed efficiently and quickly, including identifying the best solution to solve it. This study aims to simulate and visualize the TSP by developing a software simulation model. This model can be used to explain how to solve the traveling salesman problem by providing step-by-step instructions performed by users using ant colony optimization. With Windows as the operating system and the C# programming language in Visual Studio 2019, the program complies with the Extreme Programming (XP) software development method. The study concludes that optimization can be applied using programming language to provide users with comfortable and intelligible simulations and visualizations.